TEACHERS’ PERCEPTIONS TOWARD HEUTAGOGY AS THE NEW PARADIGM IN THE 21ST CENTURY EDUCATION - Khalif Rahma Riesty Fauzi; Yulianto Saba (Magister Scientiae, 2024)
Heutagogy is an educational approach that focuses on self-determined learning and the development of learner capabilities. It places the learner as the primary agent in their own learning process, emphasizing personal experience and independent exploration. In spite of the close relationship between heutagogy and Merdeka curriculum, not many Indonesian teachers are aware of heutagogy. Therefore, this study was addressing specifically how the teachers in Indonesia perceived heutagogy in teaching and learning process. The study involved collecting and analysing non-numerical data that was the results of a survey in the Google form distributed by the writer. The respondents of this study were twenty teachers of IIS SMP Progressive Bumi Shalawat. The survey results showed that most of the teachers as the participants in the study were not really aware of Heutagogy terminology although they had ideas about self-determinism, life-long learning, capability, double-loop learning, and self-reflection. Moreover, the survey results revealed that the respondents in this study were very interested in the concept of heutagogy. Hence, this study focused on the teacher's perceptions of heutagogy in learning practices.